Sodium–Glucose Co-transporter 2 Inhibitors in Heart Failure: Recent Data and Implications for Practice - Giuseppe Rosano (Radcliffe Medical Media, 2020)
Heart failure is a shared chronic phase of many cardiac diseases and its prevalence is on the rise globally. Previous large-scale cardiovascular outcomes trials of sodium–glucose co-transporter 2 (SGLT2) inhibitors in patients with type 2 diabetes (T2D) have suggested that these agents may help to prevent primary and secondary hospitalisation due to heart failure and cardiovascular death in these patients. Data from the Study to Evaluate the Effect of Dapagliflozin on the Incidence of Worsening Heart Failure or Cardiovascular Death in Patients With Chronic Heart Failure (DAPA-HF) and Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction (EMPEROR-Reduced) have demonstrated the positive clinical impact of SGLT2 inhibition in patients with heart failure with reduced ejection fraction both with and without T2D. These data have led to the approval of dapagliflozin for the treatment of patients with heart failure with reduced ejection fraction, irrespective of T2D status. This article reviews the latest data reported from the DAPA-HF and EMPEROR-Reduced trials and their clinical implications for the treatment of patients with heart failure.